Uses of a Myth: al-Andalus - Serafín Fanjul (Studies in 20th & 21st Century Literature, 2009)
In the last two decades, the Spanish press treatment of the Muslim world reflects a change of tone from unsympathetic to enthusiastic, although the information is still marred by confusion and ignorance. This change of attitude has occurred in other Western countries as well, and it is due in part to immigration trends, control over oil resources, and the relativism of official discourses towards the Third World. In the case of Spain, however, there is an additional internal element at play: the mass-media reinvention of a mythical al-Andalus as a tolerant and pluralistic society. This idealized interpretation of seven centuries of Muslim presence in the Iberian Peninsula is fraught with ignorance and distortion of the historical record but is not new. The mystification of al-Andalus has its precedent in romantic accounts that saw in “Muslim Spain” a differential fact that reinforced the exotic image of the country. It can be attributed also to the strategy to “hispanicize” al-Andalus employed by Arabists and historians to make the subject matter appealing to unsympathetic Spanish audiences conditioned by the myth of the Reconquest. Intended or not, the manipulation of the myth of al-Andalus as a historical fact has ideological and political implications that demand an objective and balanced consideration.
Keywords: al-Andalus; Spanish; Spain; Muslim; myth; Muslim Spain; Reconquest